PROTOTYPE OF AN IOT-BASED PLC CONTROL AND MONITORING SYSTEM FOR POWER SUPPLY (GENERATOR SET) AND ELECTRICITY EFFICIENCY MONITORING AS ELECTRICAL ENGINEERING LEARNING MEDIA - Muhammad Zaim Arief (Jurnal Penelitian, 2025)
Electrical equipment may be damaged or become unavailable when the supplied power exceeds system capacity or when the main electricity supply experiences a blackout. Generator sets are commonly used as backup power sources, but their limited capacity requires appropriate load prioritization. This study developed a prototype integrating a programmable logic controller (PLC), PZEM-004T electrical sensor, ESP32 microcontroller, relay modules, and a web-based monitoring interface to control priority and non-priority loads. A prototype-based experimental method was employed through whole-system functional testing, no-load testing, measurements under 5 W, 6 W, and 19 W load conditions, website data acquisition, and overload-control testing. Ten website measurements were recorded at two-second intervals for each load. The mean website power readings were 4.80 W, 5.74 W, and 18.50 W, corresponding to relative deviations of 4.00%, 4.33%, and 2.63% from the nominal load ratings. Comparison between the reference voltage measurements and website readings produced an average relative difference of 0.29%. The website displayed voltage, current, and power data consistently, while the PLC and relay system performed the intended load-control function. However, end-to-end communication latency and repeated overload-detection accuracy were not separately quantified. The prototype provides a practical platform for learning electrical measurement, PLC programming, load management, embedded systems, and IoT-based monitoring. Further research should use calibrated reference instruments, repeated overload trials, network-latency measurements, and long-term reliability testing.